PENGARUH KOMUNITAS MEREK DAN EKUITAS MEREK TERHADAP LOYALITAS PELANGGAN - Muhammad Syafruddin; Muh. Rusli Junaid (P3M STIEM BONGAYA, 2019)
The type of this research was a survey research with quantitative approach aimed at revealing (i) the effect of brand community on customer loyalty at the community of Karimun Club Makassar, (ii) the effect of brand equity on customer loyalty at the community of Karimun Club Makassar, and (iii) the effect of brand community and brand equity on customer loyalty at the community of Karimun Club Makassar. The population of this research the members of Karimun Club Community of Makassar amounted to 216 people. The sample was 68 people drawn by Slovin formulation. The data were collected by distributing questionnaires and analyzed by multiple regression. The research result indicated that (i) brand community has no effect on customer loyalty at Karimun Club Community of Makassar as proved by the P-value 0.3082 > 0.05 and the regression coefficient value -0.1194, (ii) brand equity has positive effect on customer loyalty at Karimun Club Community of Makassar, as proved by P-value 5.591e-09 > 0.05 and the regression coefficient has positive value 0.7071, (iii) brand community and brand equity have simultaneously effect on customer loyalty, as proved by the statistic value of F-test 22.683 with the significant 0.000, (iv) the value of R2 in this research is 0.3929. it indicates that customer loyalty is affected by both brand community and brand equity amounted to 39%, meanwhile the rest 61% are affected by other unobserved factors.